NILAI EKONOMI DAN KUNJUNGAN OBJEK WISATA ALAM AIR TERJUN DESA NUPABOMBAKECAMATAN TANANTOVEA KABUPATENDONGGALA - sunarti sunarti; Syukur Umar; Andi Sahri Alam (Universitas Tadulako, 2018)
Understanding Tourism, basically the scope of tourism consists of 3 elements, namely: human as a human element of tourism activities, place as a physical element that is actually covered by the activity itself and time as an element of time spent on the trip itself and while staying at the destination tour. The Tourism Sector is broadly a recreational activity outside the domicile of breaking away from routine work or seeking another atmosphere. Tourism has become an important part of the basic needs of developed countries and a small part of developing country society. Tourism is increasingly developing in line with social, cultural, economic, technological and political changes As a human activity, tourism is a very complex phenomenon of the movement of people, goods, and services. Tourism is closely related to organizations, institutional and individual relationships, service needs, and so on. The purpose of this study is to find out the factors that influence the intensity of visits and calculate the economic value of Nupabomba Waterfall Nature Tourism Objects based on the method of travel costs. The location of this research was carried out in the Natural Tourism Object of Nupabomba Waterfall in Tanantovea District, Donggala Regency. The sample used in this study was purposive sampling using the analysis of the Travel cost method. Based on the results of the research conducted the magnitude of the economic value of the Tumanggu Indah Waterfall Tourism Object using the trip cost method was 189,632 / visit with Visit Intensity 3 times.Keywords: Economic Value, Waterfall Nature Tourism, Nupabomba Village.